THE RELATIONSHIP BETWEEN DIET AND FAMILY SUPPORT TO BLOOD SUGAR IN DIABETES MELLITUS PATIENTS IN SUMBERBERAS HEALTH CENTER - Agatha Widiyawati; Puspita Puspita (Jurnal Delima Harapan, 2023)
Diabetes mellitus (DM) is a disease of insulin sensitivity disorders where the body is unable to produce insulin. The purpose of this study was to analyze the diet (3J namely the right amount, type and schedule) which is adherence to the DM diet and family support for sugar levels in type 2 DM patients. This research method is a cross sectional design with a population of 44 people. The sampling technique uses a sample quota.The instruments used were the 1x24 hour food recall form and the family support form.Statistical analysis using SPSS 25 with Spearmen test.The results of the study obtained a p-value > 0.005 for the amount of intake (energy, protein, carbohydrates) and type of blood sugar, while the p-value < 0.005 for the amount of intake (fat), meal schedule and family support for blood sugar levels.The conclusion of this study is that there is no relationship between the amount of intake (energy, protein, carbohydrates), there is a relationship between the amount of intake (fat), there is no relationship between types, and the more adherent to the meal schedule and good family support, the lower the blood sugar level.